Drawing the heroes in your graphic novel - Lee, Frank, 1980- (Lee, Frank, 1980- How to draw your own graphic novel (PowerKids Press), 2012)
Provides step-by-step instructions on drawing the main character of a graphic novel or comic, providing examples of heroes, including a caped superhero and good cop.